A Multilevel Structural Equation Model of Within- and Between-Person Associations among Subjective Responses to Alcohol, Craving, and Laboratory Alcohol Self-Administration - Wardell, Jeffrey D. (J Abnorm Psychol, 2015)
Subjective responses to alcohol are important determinants of drinking behavior and have been linked with risk for alcohol use disorders. However, few attempts have been made to examine proximal within-person associations among state changes in subjective responses and ongoing alcohol self-administration in the laboratory. This study disaggregated within- and between-person associations among subjective responses and alcohol self-administration, while also examining the mediating role of craving and the moderating role of trait impaired control over alcohol. Sixty young heavy drinkers (mean age=19.90, SD=0.86) completed self-report measures including the Impaired Control Scale, then participated in a 2-hour intravenous alcohol self-administration session using the Computer-Assisted Self-infusion of Ethanol (CASE) paradigm. Repeated assessments of subjective stimulation, subjective sedation, and craving were examined in relation to ongoing in-session self-administration, as indexed by breath alcohol concentration (BrAC) assessed 15 minutes later. Multilevel structural equation modeling was used to disentangle within-person and between-person associations. The results showed few significant associations at the between-person level, except for a direct negative association between sedation and BrAC. At the within-person level, state fluctuations in stimulation were positively associated with both craving and subsequent BrAC, whereas state changes in sedation were negatively associated with craving and positively associated with BrAC. Within-person indirect associations from subjective stimulation and sedation to subsequent BrAC mediated via craving were statistically significant. Also, participants higher on impaired control showed stronger within-person associations between craving and greater subsequent BrAC. The results suggest that subjective responses to alcohol and craving have proximal associations with self-administration behavior, the strength of which is linked with trait impaired control over alcohol.